2019
DOI: 10.2147/cmar.s201975
|View full text |Cite
|
Sign up to set email alerts
|

<p>Human papillomavirus DNA in surgical smoke during cervical loop electrosurgical excision procedures and its impact on the surgeon</p>

Abstract: Objective: The purpose of this study was to explore whether human papillomavirus (HPV) DNA is present in surgical smoke generated by loop electrosurgical excision procedures (LEEPs). Furthermore, we investigated the impact of this HPV DNA on surgeons. Methods: A total of 134 outpatients with persistent HPV infections treated with LEEP for cervical intraepithelial neoplasia between 2015 and 2016, along with the corresponding LEEP operators, were included. The flow fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 29 publications
(29 reference statements)
1
84
0
1
Order By: Relevance
“…The presence of Hepatitis B virus (HBV)/HCV/HIV/HPV Deoxyribonucleic acid (DNA) in surgical smoke has been well proven in multiple studies. [1][2][3] HPV transmission during anogenital surgery is most widely reported in the literature. Liu et al outlined four articles linking surgical smoke to the transmission of HPV (type 6,11,13), progressing to oropharyngeal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of Hepatitis B virus (HBV)/HCV/HIV/HPV Deoxyribonucleic acid (DNA) in surgical smoke has been well proven in multiple studies. [1][2][3] HPV transmission during anogenital surgery is most widely reported in the literature. Liu et al outlined four articles linking surgical smoke to the transmission of HPV (type 6,11,13), progressing to oropharyngeal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the presence of human immunodeficiency virus (HIV), human papillomavirus (HPV), hepatitis B surface antigen (HbSAg) and hepatitis C virus (HCV) in the cautery smoke. [1][2][3] Research has shown the presence of SARS COV-2 in feces, blood, peritoneal fluid and mucosa. 4 SARS-CoV-2 Ribonucleic acid (RNA) has been found in the feces of infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…When healthcare staff risk was investigated, Weyandt and Zhou have shown that samples taken from the operating surgeons were positive for viral DNA from HPV. 18,21 However, there were differences shown within these studies as Weyandt found that viral DNA obtained from operators was not consistent with that of the patients they were operating on. 18 In contrast to this, Zhou demonstrated consistency between operator and patient viral DNA subtypes.…”
Section: Discussionmentioning
confidence: 93%
“…This raises the concerns of spread of infection from inhalation of surgical smoke during the use of electrosurgery and CO 2 used for the creation and maintenance of pneumoperitoneum. [12][13][14] Surgical smoke has been demonstrated to have viral deoxyribonucleic acid, but the inhalation of smoke resulting in disease has not been adequately evaluated. There are reports of identifying human papilloma virus, human immunodeficiency virus, and hepatitis B virus in surgical smoke, but their infectivity is unknown and hence universal precautions are recommended during surgery.…”
Section: Aerosol and Surgical Smokementioning
confidence: 99%